Judicial Powers and Functions of Military and Civil Governors of Orenburg Governorate in Late 18th - First Third of 19th Century - N. L. Semenova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to the analysis of judicial functions of military and civil governors of Orenburg governorate in the late 18th - first third of 19th century. The novelty of the research is determined by the introduction of new materials of record-keeping into scientific usage, which characterize the judicial practice of Orenburg military and civil governors. The author paid special attention to the problem of legislative differentiation of judicial powers of military and civil governors of the Orenburg governorate, which was completed by the early 1820s. It is shown that the model of the judicial system, which developed in the Orenburg governorate in the late 18th - first third of 19th century, had a number of features associated with the presence of the power of military and civil governors, as well as a significant proportion of the indigenous non-Russian population. Particular attention is paid to solving court cases against the Bashkir and Mishar population, which were associated with service orders, criminal offenses committed during the service, abuse of officials. It is shown that the military and civil governors could not change the decisions of the judicial bodies of the governorate. The author comes to the conclusion that judicial functions occupied a significant place in the activities of the supreme administration of the region and provided for a sufficiently effective implementation of the legislation of Catherine II and Alexander I.